Social identity management and integration amongst indigenous African refugee minorities in Norway : the case of Kvæfjord kommune - Marambanyika, Ocean (Universitetet i Tromsø, 2008)
This thesis principally deals with issues of social identity management and integration amongst African refugee minorities in Norway. Employing an analytical strategy, the thesis explores varying complex and inter-related situations faced by indigenous African refugees in Norway and how these situations presents challenges in social identity management by the refugees. This piece of work specifically focuses on analyzing how the refugees in question employ social identity management variables like ethnicity, regionalism, language, religion, food, clothing, gender, music and imagined idealizations in managing their social identities. The thesis argues that different situations in the refugee`s host community and the camp environment have impacted into the refugees, dispositions to act differently depending with the objective and extricate demands of the varying situations. Integration as a practical concept has been equally co-opted into the thesis with a design to analyse the impact of integration programmes on refugee social identity management processes. The Kvæfjord Commune, in collaboration with some civil society organizations in its municipality has fashioned some integration programmes in an endeavor to integrate the refugees into the mainstream societal functionalisms. It is nevertheless argued that the outcomes of such integrative approaches has created complex and over-lapping conditions which have multi-directionally impacted on the refugee social identity management processes. Whilst recognizing and building on related works on ethnicity and social identity, the thesis finds a unique position by venturing into the study of a multi-nationalized inter-continental refugee camp set-up which has been minimally deliberated upon especially with regard to the social identity management arena.